Groundwater Quality Assessment for Drinking Purpose of Taluka Chachro, Thar Desert, Pakistan; Using Water Quality Indices, and Geospatial Techniques - Samtio, Muhammad Soomar; Hakro, Asghar A.A.D.; Mastoi, Abdul Shakoor; Rajper, Riaz Hussain; Agheem, Muhammad Hassan; Lashari, Rafique Ahmed (International Journal of Economic and Environmental Geology, 2022)
Groundwater quality of taluka Chachro was investigated by analyzing thirty-two groundwater samples for drinking purpose. Multivariate statistical approaches with GIS interpolations (IDW) were applied for the identification of significant geochemical processes governing the groundwater quality.. Results showed the concentrations of physiochemical parameter in the study area exceeded the prescribed level of WHO guidelines. The EC and TDS varied from 2593-18950 μS/cm and 1659-12128 mg/l, respectively. The Ca, Mg, Na, and K range from 36-288, 17-272, 420-3280, and 9.5-101 mg/l, respectively. While, Cl, HCO3, SO4, and NO3 varied from 539-5738, 210-1150, 79-870, and 6.66-17.13 mg/l respectively. The mean values of EC, TDS, Na, Cl, HCO3, SO4, and NO3 were higher than the prescribed level of WHO 2011. Higher concentrations above the acceptable limits were recorded for K 96.15%, SO4 88.46%, and HCO3 82.16% of analysed samples. Multivariate statistical analysis suggested that the input of natural processes have influenced groundwater quality which resulted in changing the groundwater chemistry of taluka Chachro. The results revealed the dominant trend among the cations was Na>Ca>Mg>K while among the anions it was Cl>HCO3>SO4. Based on the drinking water quality index 50% were unsuitable for drinking. Keywords: Thar desert, groundwater, WQI, GIS interpolation, geochemical processes.